Partisipasi Masyarakat dalam Program Pelestarian Lingkungan di Kawasan Bendhung Lepen Kampung Mrican, Kota Yogyakarta - Dewanti, Isabell Nur Fadhilla; Permana, Raden Chrisna Trie Hadi; Andini, Isti; Kusumastuti (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Community participation refers to the active involvement of citizens in various stages of the development process, especially at the village level. A concrete example of community participation can be seen in the case study of Bendhung Lepen, located in Mrican Village, Yogyakarta. Bendhung Lepen is an irrigation canal that stems from the Gajah Wong River. Before its revitalization, the area faced numerous environmental problems, primarily due to household waste and pollution that contaminated the waterway and negatively affected the environment and public health. In response to these issues, local residents, along with relevant stakeholders, initiated an environmental conservation program. The main goal of this initiative was to restore the ecological function of Bendhung Lepen and transform it into a clean, green, and beneficial public space for the community. This study aims to measure the level of community participation in the environmental conservation program. Data collection methods included questionnaires for quantitative analysis and in-depth interviews for qualitative insights into community involvement. The results of the study show that community members were actively involved in various phases of the program, including planning, implementation, and evaluation. Stakeholders involved in the program included community leaders, youth groups, environmental organizations, and village officials. The forms of participation extended beyond voicing aspirations to contributing labor (through mutual cooperation) and materials (such as donations or supplies). According to Arnstein’s ladder of participation, the level of community participation in this conservation program falls under the category of